Peran Elit Tradisional Tigo Luhah Tanah Sekudung dalam Pemilihan Kepala Daerah Kabupaten Kerinci Tahun 2018: Analisis Peran Aktif, Partisipatif, dan Pasif - Wahyu Hidayat; Sri Yunanto; Asep Setiawan (Yayasan Literasi Sains Indonesia, 2025)
This research analyzes the role of the traditional elites of Tigo Luhah Tanah Sekudung in the 2018 Regional Head Election in Kerinci Regency. The background of the study is the significant role of traditional elites in winning the 2018 Kerinci Regency regional election contest. The research aims to identify and understand how the traditional elites of Tigo Luhah Tanah Sekudung played a role in the 2018 regional election in Kerinci Regency. This study uses a descriptive qualitative method with a data triangulation approach, including in-depth interviews, document studies, and direct observation of political activities in the field. The results of the study show that the role of the traditional elites of Tigo Luhah Tanah Sekudung significantly influenced the election and victory of the regent and vice-regent candidates in Kerinci in 2018. The elites played three forms of roles: active, participatory, and passive (based on Lewis A. Coser's causal role theory). The findings successfully answered the important role of elites in the regional election.In conclusion, the role and involvement of traditional and religious elites were crucial and able to integrate the residents of Tigo Luhah Tanah Sekudung to vote for and support the regent and vice-regent candidates, leading to their election and victory in the 2018 regional election. This research provides practical contributions to the development of political strategies and recommendations for politicians facing elections, especially in regions that still uphold traditional values, such as Kerinci Regency.